Psychometric Properties of the Psychological Vulnerability Scale in Higher Education Students - Nogueira, Maria José (2020)
Submitted by Orísia Pereira (orisia@esenf.pt) on 2020-06-16T10:09:39Z No. of bitstreams: 1 artigos afiliados-65.pdf: 145094 bytes, checksum: 59f3b51a906e56ed738ed5d239c1a166 (MD5)